Explore the perception of millennial generation about csr in fashion luxury brands - Pinto, Maria Clara Laso (2015)
Each generation has unique specificities. People has change over time and all of them impose new attitudes, lifestyles, ways of thinking, and all of them bring something new to the society and the world. The millennial or Y generation (aprox. 1978- 2000), are people well informed and very involved with new technologies and communication tools. They live in a constant change and are always interacting between them and with the brands that they like. Y's have grown up with a conscious of being sustainable in order to have a better lifestyle, and to live in a better world. When it comes to the responsible corporate practices, millennial are also concerned about having things transparent and helping the business and the society to improve, so their sustainable and responsible attitude is also present there. Therefore, nowadays corporations which are being managed or which have some advices from Y's, are being more socially responsible and consequently are being more sustainable and profitable through the time. Although fashion luxury brands have a different way of managing their business comparing with the rest of brands, as in the way they approach to their customers and particularly in the way of doing marketing communication; the main aim will always be the same which is to boost their profits. Corporate social responsibility would be a helpful tool to improve the core business if the company uses all of these good practices correctly. That means not only fixing things after the damage but preventing some actions before they occur, and having a good control over all the value chain.